Effect of combination nutrition supplement on HSP72 in periphal blood of women boxers during weight loss before competition - Hou, X.; Wang, J.; Cai, A.; Ge, X. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was try to find a combined nutrition supplement, which can help loss the weight and improve physical capability at the same time, through observe the effect on Hsp72 in peripheral blood of L- carnitine, branched-chain amino acid (BCAA) and glutamine(Glu) use together. Conclusion: L- Carnitine, Branched-chain Amino Acid (BCAA) and Glutamine(Glu) combined supplement can help fatty burning and loss weight, alleviate the badness of weight loss, and improve the stress ability of women boxers, but the dosage should be careful.